Pelatihan Pemanfaatan Media Pembelajaran Daring Dimasa Pandemi Covid-19 bagi Guru Sekolah Dasar di Kecamatan Loura - Ferdinandus Bele Sole; Desak Made Anggraeni; Yohanis Umbu Kaleka; Etheldreda Rosari Garung; Margareta Alfonsa Theedens; Roswita Andriane Rato (Pascasarjana Universitas Mataram, 2022)
Online Learning Media Utilization Training Activities during the Covid-19 Pandemic for Elementary School Teachers in Loura District aim to improve teachers' knowledge and skills in using online learning media during the Covid-19 pandemic. The method used in this activity adopts a problem-solving learning model where each participant is given a problem related to the training material, then the trainee is asked to solve the problem and continue with the discussion activity classically. This activity began with a discussion activity with representatives of elementary school teachers in Loura subdistrict about learning problems carried out during the Covid-19 pandemic. Furthermore, an introduction to online learning media that can be used in the learning process and then the participants are trained about the techniques for using online learning media. This training activity provides understanding to trainees about the use of online learning media in the teaching and learning process, especially in the learning process during the Covid-19 pandemic. Participants of the training activities gave a positive response to the implementation of this training activity because they obtained knowledge related to the use and utilization of online learning media to help them in the learning process during the Covid-19 pandemic in their respective schools.